Targeting the tumor microenvironment to improve clinical outcomes in triple negative breast cancer patients and bridge the current disparity gap - Alharbi, Malak; Roy, Arya Mariam; Krishnan, Jayasree; Kalinski, Pawel; Yao, Song; Gandhi, Shipra (Frontiers in Immunology, 2024)
Triple negative breast cancer (TNBC) is a heterogenous disease that disproportionately affects Black women. TNBC outcomes among Black women are dismal secondary to multiple factors, such as poor healthcare accessibility resulting in delays in diagnosis, and aggressive disease biology in addition to a pro-tumor immune microenvironment (TME). Black women with breast cancer exhibit elevated levels of serum pro-inflammatory cytokines, and a pro-tumorigenic TME with higher immunosuppressive regulatory T cells (Tregs), M2 macrophages and exhausted CD8+ T cells. We have shown that the combined use of toll-like receptor 3 (TLR3) ligands with interferon-α (chemokine modulation: CKM) is able to enrich the tumor with CD8+ T cells, while not increasing immunosuppressive cells. Recent clinical trials have revealed the efficacy of immune checkpoint inhibitors (ICI) in rejuvenizing exhausted CD8+ T cells. We hypothesize that strategies to modulate the TME by enriching chemokines that attract CD8+T cells followed by reversal of CD8+ T cell exhaustion (ICI), when added to standard treatment, could potentially improve clinical outcomes, and mitigate the racial disparities in TNBC outcomes between Black and White Women.